Influence of hollow carbon microspheres of micro and nano-scale on the physical and mechanical properties of epoxy syntactic foams1. Issue 63 (10th July 2015) - Li, Xiudi; Zhu, Ming; Tang, Xuemei; Zhang, Qingjie; Yang, Xiaoping; Sui, Gang
<x xml:space="preserve">Abstract</x> The introduction of hollow carbon microspheres at different content and particle size led to various impacts on the physical and mechanical properties of epoxy syntactic foams due to the diversity in the interfacial interactions and microstructure.